Characteristics Of Student Learning Styles And Learning Behavior Orientation (Case Analysis of Learning Behavior of Social Studies Education Students UIN Jember) - Sutomo, Moh. (FALASIFA : Jurnal Studi Keislaman, 2025)
Based on the results of observations and direct interaction with students of the Social Studies Education Study Program of UIN KHAS Jember as many as 65 students, both male and female, who are still active from semester 2 to semester 6 for 3 months, this study found that the results of student understanding of certain courses are greatly influenced by the learning system provided by the lecturer. The more the lecturer gives many reasoning tasks and also summarizes the material, the student's interest in learning also increases. In addition, the more creative the lecturer is in using learning methods, the more active and easier it is for students to achieve the expected learning objectives. However, whether the 65 students who were used as respondents can grasp the material quickly, moderately or slowly, this is what is interesting to study. The results of the hypothesis in this study, effective learning methods and strategies are needed to achieve learning objectives that can be obtained by each student. So to be able to teach well, before teaching a teacher must be able to answer three main questions, namely: 1) will students be able to learn?, 2) how to organize students so that they can achieve their learning objectives well?, 3) what things must be done related to individual differences that students have? Using a phenomenological approach, this study concludes that in the context of higher education, visual learning styles, auditory learning styles, and kinesthetic learning styles have a positive relationship or influence on student learning behavior in understanding learning materials. Increasing understanding of visual learning styles, auditory learning styles, and kinesthetic learning styles is one of the crucial aspects in preparing students to become competent and effective educators in today's educational context.